#### Answer

$w+z$
= $- 1 + 6i$
See Graph I for the geometric representation

#### Work Step by Step

$w = 3 + 5i$, $z = - 4 + i$
$w+z$
= $3 + 5i + (- 4 + i)$
= $3 + 5i - 4 + i$
= $- 1 + 6i$
See Graph I for the geometric representation

Published by
Pearson

ISBN 10:
978-0-13-421743-7

ISBN 13:
978-0-13421-743-7

$w+z$
= $- 1 + 6i$
See Graph I for the geometric representation

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.